Impact of water mills on rural livelihood: A study of Arunachal Himalaya - N J Thongdok; V P Sati
The Himalayan people have a rich ancient tradition and heritage of utilizing water mills (Chhoskor) for grinding purposes. The Shertukpen inhabits in the western and south-western parts of the West Kameng district of Arunachal Pradesh, Eastern Himalaya. It is an indigenous tribal group. They are carvers and experts in carving wood and stone. The purpose of this paper is to examine the rich culture of grinding practices through water mills (Chhoskor) by the Shertukpen hence, the practices of traditional watermills have an immense influence on the socio-economic and livelihood aspects of the society. It also examines how this traditional grinding practice is impacting the livelihood of rural areas. The major grinding products are food grains, fruits, vegetables, and other related products. The methods used in this study were interview, focused group discussion, and observation. A field visit was made in July 2022. The study shows that the tools of grinding are now become endangered and vulnerable. These require attention and study for preservation, whereas, the grinding practices have a huge socio-economic impact on rural areas.